Elite athletes’ overall oral health, values and related quality of life: a cross-sectional study - André Júdice; Diogo Brandão; João Botelho; Vanessa Machado; Luís Proença; Luciano M. A. Ferreira; Athanasios Stamos; Peter Fine; José João Mendes (Scientific Reports)
Abstract The present observational study aimed to identify the prevalence of oral health issues in this population and explore the relationship between oral health and factors relevant to athletic performance. One hundred and fourteen elite athletes triaged at a Sports Dentistry department from a university clinic were included for oral health assessment, self-reported periodontitis, basic erosive wear examination, and dental caries experience. They answered a sociodemographic questionnaire, oral health impact profile 14 to measure OHRQoL and OHV scale. Descriptive and inferential statistics assessed oral health outcomes and demographic or sport-related factors. Multivariable logistic regression explored predictors of poor oral health outcomes. The results reveal a high prevalence of oral health issues among elite athletes, with over half of the participants (51.8%) presenting two or more pathological or functional findings. Periodontal disease (55.1%), particularly gingivitis (51.8%), and dental caries (47.4%) were the two most common conditions, affecting nearly half of athletes. This high prevalence of oral conditions did not associate with worse OHRQoL and OHV. These results suggest that elite athletes face unique challenges regarding oral health, with some sex differences in oral health behaviors. Despite the high prevalence of oral diseases, related quality of life and values did not show any association, possibly due to the low perception of athletes.